2021
DOI: 10.1038/s41598-021-81655-0
|View full text |Cite
|
Sign up to set email alerts
|

EEG signals respond differently to idea generation, idea evolution and evaluation in a loosely controlled creativity experiment

Abstract: Many neurocognitive studies endeavor to understand neural mechanisms of basic creative activities in strictly controlled experiments. However, little evidence is available regarding the neural mechanisms of interactions between basic activities underlying creativity in such experiments. Moreover, strictly controlled experiments might limit flexibility/freedom needed for creative exploration. Thus, this study investigated the whole-brain neuronal networks’ interactions between three modes of thinking: idea gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 109 publications
0
35
0
2
Order By: Relevance
“…It is commonly observed that centro-parietal alpha power decreases in tasks with visually presented stimuli. Several studies have demonstrated that generation of ideas in the figural domain is related to the strong decrease in the upper alpha activity at parietal site, which reflect the high visuospatial processing requirements during mental generation and manipulation of visual representation 62 , 63 . In the field of mathematics, researchers found that the parietal site supports magnitude manipulations in arithmetic tasks 64 .…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly observed that centro-parietal alpha power decreases in tasks with visually presented stimuli. Several studies have demonstrated that generation of ideas in the figural domain is related to the strong decrease in the upper alpha activity at parietal site, which reflect the high visuospatial processing requirements during mental generation and manipulation of visual representation 62 , 63 . In the field of mathematics, researchers found that the parietal site supports magnitude manipulations in arithmetic tasks 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The power socket consists of 4 individual sockets, and any one of them can be controlled independently. Raw EEG signals, which are the constantly fluctuating potential variance between the negative and the positive electrodes, are captured by the EEG headset from the user's brain, and the algorithm isolates individual brain waves such as low alpha, high alpha, low beta, high beta, delta, theta, low gamma, and mid gamma by applying a series of digital filters to the reported signal [23], and this concept is as illustrated as in Figure 4. Recent advances in signal processing and machine learning technologies have enabled computer systems to undertake further complex tasks, such as EEG data analysis.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…The loosely controlled setting refers to considerable freedom regarding response time (self-paced) and response action (integrating thinking and drawing phases) while maintaining certain degrees of control 40 . The effectiveness of loosely controlled settings was demonstrated in a recent creativity study 17 . To align our findings with other validated evidence, we investigated the regional contribution of brain oscillations in the classical frequency bands (delta, theta, alpha, and beta) to the different open-ended creation tasks through TRP analysis.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in cognitive workload frequently occurs at the beginning and end of idea generation 20 , 21 , an effect that influences the subjective rating of task difficulty 22 . Compared to idea generation, increases in alpha power are associated with idea elaboration and idea evolution 17 , 23 . In addition, idea evaluation is associated with increased theta power over mid-frontal sites, reflecting heightened cognitive control 24 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation